Unraveling the mystery of dieback in Dalbergia sissoo: a review - Muhammad Zunair Latif; Amer Habib; ChongChong Lu; Xinhua Ding (Phytopathology Research)
Abstract The shisham tree (Dalbergia sissoo) is a keystone hardwood species of South Asia, highly valued in economic value in forestry, agroforestry, and landscape horticulture due to its durable, fragrant, and decay-resistant wood. However, shisham's health on both public and private lands is seriously compromised by recurrent outbreaks of dieback disease. Shisham has a history of severe dieback over the last century throughout its natural and introduced range. Since 1918, mortality associated with shisham dieback has been studied to determine its spread and underlying causes. Like most pathosystems, shisham dieback involves complex interactions among multiple biotic and abiotic factors, with certain site- and stand-level factors exacerbating disease severity across various regions and times. Recent outbreaks of shisham dieback in Pakistan have been linked to Ceratocystis dalbergicans. Previously, Fusarium was linked to wilt/dieback disease in Shisham. This disease has been differentiated from often-confusing Fusarium wilt/dieback on the same plant and explains dieback, a separate disease of shisham. Currently, published guidelines for managing Ceratocystis infections in shisham are limited. While researchers have explored potential management strategies, including identifying host resistance genes and chemical control methods, achieving sustainable disease control will require long-term, dedicated efforts due to the extended lifespan of shisham trees. This review provides a historical and updated perspective on the investigation and establishment of the pathogenic basis of shisham dieback, focusing on the role of Ceratocystis species. This work aims to clarify existing knowledge gaps, resolve controversies surrounding disease causation, and inform future research to enhance shisham conservation efforts.